Dyspnea in the Supine Position after Anterior Cervical Discectomy and Fusion - Zhang, Hua (The Surgery Journal, 2018)
Posterior occipitocervicothoracic fusion in a flexed position may cause dyspnea, and the onset of obstructive sleep apnea after anterior upper cervical fusion. However, there are no reports of dyspnea occurring after anterior lower cervical fusion. Here, we present an unusual case of dyspnea in the supine position after a C5-C6 anterior cervical discectomy and fusion.
Keywords: dyspnea; anterior cervical discectomy and fusion; pharyngeal; obstructive sleep apnea; soft tissues